A Scoping Review of the Perceptions and Experiences of People From Underserved Groups of Being on Personalized Stratified Follow-Up Following Treatment for Breast Cancer - Katie Sutton; Sophie McGrevey; Verna Lavender; Lorraine Marke; Jo Armes (Cancer Nursing, 2026)
Background: Personalized Stratified Follow-Up (PSFU) is an approach to cancer follow-up involving patients re-accessing care when they need to, rather than attending predetermined appointments. The benefits of this approach are a more personalized experience for patients and increased capacity in clinics. Objective: To understand the evidence relating to the experiences of people on PSFU following breast cancer treatment, specifically in terms of the perceptions of people from underserved groups. Methods: A scoping review of the relevant evidence was conducted. Screening was conducted independently by 2 researchers. Data extracted were charted using a predetermined checklist for summary and analysis. Results: A total of 2728 results were identified through databases; 11 papers were included. Nineteen gray literature resources were also identified. Findings were presented as: (1) key components of PSFU for breast cancer; (2) experiences and perceptions of patients and health professionals in relation to PSFU for breast cancer; (3) suggestions to enhance PSFU; and (4) evidence relating to underserved groups on PSFU for breast cancer. Conclusion: Patients on PSFU are generally satisfied with their care and are confident in managing their own condition. Unmet needs include psychological support and re-accessing clinical teams. This review has highlighted that little is known about the experiences of underserved groups. Implications for Nursing Practice: Nurses should be aware of the importance of providing patients on PSFU with information about self-examination, signs of recurrence, side effects, and re-accessing the clinical team. PSFU services should be designed to ensure that patients from underserved groups do not experience inequalities in their care.